The clinical profile of dengue infection cases presenting in a tertiary care institute: an observational study - Shrivastava, Kiran; Ojha, Sakshi; Nadkarni, Jayashree (International Journal of Contemporary Pediatrics, 2018)
Background: Dengue is a mosquito-borne viral disease that has rapidly spread in all regions of WHO in recent years. It is an acute febrile illness, caused by infection with any of 4 related positive-sense, single-stranded RNA viruses of the genus Flavivirus, dengue viruses 1, 2, 3, or 4. Objective of study was to study the clinical profile of dengue viral infection in the paediatric age group. Methods: This observational study was conducted in a tertiary referral centre in Central India. Cases were classified based on the WHO 2009 Dengue guidelines for diagnosis, treatment, prevention and control and the clinical and laboratory parameters were analyzed for demographic and other correlates. Results: 75 patients met all the inclusion criteria and were analyzed. Most children were in age group 6-10 years. Fever, bleeding, rash, abdominal pain and vomiting were the common symptoms. We noted some atypical symptoms also. Conclusions: When infected, early recognition and prompt supportive treatment in dengue infection can substantially lower the risk of medical complications and death.